2010
DOI: 10.1037/a0018962
|View full text |Cite
|
Sign up to set email alerts
|

How does cognitive control reduce anger and aggression? The role of conflict monitoring and forgiveness processes.

Abstract: It is well-established that superior cognitive control abilities are associated with lower levels of anger and aggression. However, the precise emotion regulation operations underlying this relationship have been underspecified and underexplored in previous research. Drawing on neuropsychological models of cognitive control, the authors propose that limited capacity resources can be recruited within a hostile situation to promote a process of forgiveness. The results of 2 studies supported this proposal. Acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 65 publications
5
91
0
3
Order By: Relevance
“…Compassion may reduce desires for punishment by enhancing cognitive control (cf. Pronk, Karremans, Overbeek, Vermulst, & Wigboldus, 2010;Wilkowski, Robinson, & Troop-Gordon, 2010), situational attributions for a transgression (cf. Rudolph et al, 2004) or intuitions of perceived similarity with the transgressor (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Compassion may reduce desires for punishment by enhancing cognitive control (cf. Pronk, Karremans, Overbeek, Vermulst, & Wigboldus, 2010;Wilkowski, Robinson, & Troop-Gordon, 2010), situational attributions for a transgression (cf. Rudolph et al, 2004) or intuitions of perceived similarity with the transgressor (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Stillwell, Baumeister, and Del Priore (2008) argued that a goal of vengeance is to restore equity after a provocation and found evidence to suggest that avengers actively seek out methods to hurt a transgressor. Wilkowski, Robinson, and Troop-Gordon (2010) found that vengeance was a significant mediator between effortful control and aggressive behavior. Other studies have found that revenge motivation partially mediates the effect of violent video games on immediate aggressive behavior and on trait aggressiveness (e.g., Anderson et al, 2004;Anderson & Murphy, 2003).…”
Section: Possible Mediators Between Reappraisal and Aggressive Behaviormentioning
confidence: 97%
“…Specifically, participants low in trait anger showed a reduced interference effect on a Flanker task (i.e., a measure of cognitive control) following hostile word primes relative to participants high in trait anger. In a second set of studies, they found that this ability to automatically recruit cognitive control predicted motivation to forgive interpersonal transgressions [28]. Thus, improving cognitive control should help aggressive people inhibit the desire to harm other people when angered.…”
mentioning
confidence: 98%